The Effect of Cheating Culture on the Implementation of State Defense at Politeknik Negeri Jakarta - Respati Prajna Vashti; Syan Rosyid Adiwinata; Nesta Sbastian (SOSHUM : Jurnal Sosial dan Humaniora, 2022)
Based on the results of observations to students, it was found that cheating is an entrenched habit among students. This is not in line with the efforts made to avoid cheating, including by preparing to study before the exam to understand the material better. This study aims to determine the effect of cheating culture on students, as an implementation of state defence. This study uses a quantitative descriptive method with the type of survey research. Conclusions are made through the analysis of questionnaires from respondents. The data sources are taken from 3rd-semester students. The sample is determined by using random sampling, the student population is 150 students which is divided into 7 engineering and non-engineering students. The result of this study shows that 87.8% of students had cheated with the factors of lack of self-confidence and fear of bad grades. Then, 99% of students stated that honesty is one of the behaviours that can reduce the cheating habit. Honesty is considered as a form of state defence implementation at Jakarta State Polytechnic students which must be carried out consistently, as the goal of forming national character can be achieved as an effort to face challenges in the future.